Applying social learning where ‘business-as-usual’ solutions no longer work for complex problems and programs - Le Borgne, Ewen (2016)
Key messages • Social learning facilitates sharing and learning beyond individuals to networks and systems. Through a facilitated, iterative process of joint work, dialogue and reflection, new shared ways of knowing emerge that lead to changes in practice. • Social learning has real potential to unlock change and transform relationships between actors involved in complex programs and/or dealing with ‘wicked problems’. Adversely it is not advisable to pursue for simple initiatives. • Social learning offers many thematic and pragmatic entry points to be embedded in the CGIAR research programs around partnerships, innovation systems, monitoring and evaluation.